Putaminal Hypointensity in the Parkinsonian Variant of Multiple System Atrophy: Simple Visual Assessment Using Susceptibility-Weighted Imaging - Lee, Jae-Hyeok (The Korean Movement Disorder Society, 2011)
BACKGROUND AND PURPOSE: Susceptibility-weighted imaging (SWI) has been shown to be superior in its ability to demonstrate brain mineralization than other conventional MR imaging. The goal of our study was therefore to assess the frequency and extent of putaminal hypointensity in parkinsonian variant MSA using SWI. METHODS: 11 patients with multiple system atrophy-parkinsonian type (MSA-p), 30 patients with Parkinson’s disease (PD), and age matched 30 controls were investigated using 3 Tesla MRI. The pattern of putaminal hypointensity was measured using a visual grading scale and scored from 0 to 3. RESULTS: Hemi- or bilateral putaminal hypointensity (a score of ≥ 2) and hyperintense rim were recognized in 81.8% and 54.5% of 11 MSA-p, respectively. The scores of putaminal hypointensity of MSA-p were significantly higher than other groups (p < 0.001), a score of ≥ 2 differentiated MSA-p from other groups. And all five patients with early disease stage also showed these characteristic findings. CONCLUSIONS: SWI appears to be useful for depicting putaminal hypointensity even in early stage of MSA-p. This finding suggests that iron deposition associated putaminal degeneration can occur early in the disease process.